KOLABORASI DAN PRODUKTIVITAS PENULIS ARTIKEL VISI PUSTAKA 2000 – 2014 - Nani Rahayu, Rochani; Rachmawati, Rulina (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2015)
Visi Pustaka is one of the Library and Information Science (LIS) journals in Indonesia. Study about this journal needs to be done to find out the progress in Library and Information Science in Indonesia. This paper reviewed Visi Pustaka journal especially about the amount of articles, gender, collaboration degree, collaboration frequency, productivity, and author affiliation. Data collected from Visi Pustaka journal articles which published in 2000-2014 periods. Data analyzed using statistic descriptive method. The result showed that the amount of article published in 2000-2014 periods were 236 articles, about 65.64%written by men and 34.36% written by women. Average degree of collaboration was 0.097. The most productive authors were Sulistyo Basuki and B. Mustafa. Both of them submitted 16 articles. The most five productive affiliation were Bogor Institute of Agriculture (14.38%), Indonesian National Library (11.45%), Indonesian University (12.60%), Centre for Scientific Documentation and Information (8.02%) and Gadjah Mada University (6.11%). The affiliation status consisted of 212 (80.91%) government institutions and 50 (19.09%) was private organizations. We cloncluded that most gender of author was men, most of the articles wrote by individual authors, and most author affiliations were library and information institutions also universities.